Regioselective monoalkylation of dimethyl alkylidenesuccinates: simple approach to dialkyl-substituted maleic anhydrides including chaetomellic acid A - Kshirsagar, Umesh A.; N. P. Argade (Synthesis-Stuttgart, 2011)
Natural and nonnatural dialkylmaleic anhydrides were readily prepared from dimethyl alkylidenesuccinates by sodium hexamethyldisilazide-induced selective monoalkylation followed by base-catalyzed hydrolysis.
Keywords: alkylations; Esters; furans; heterocycles; maleic anhydrides